Dietary carbohydrate-to-protein ratio influences growth performance, hepatic health and dynamic of gut microbiota in atlantic salmon (Salmo salar) - Villasante Urquiza, Alejandro.; Ramírez, Carolina; Rodríguez, Héctor; Dantagnan, Patricio; Hernández, Adrián J.; Figueroa Villalobos, Elías.; Romero, Jaime (KeAi Communications Co., 2022)
Atlantic salmon (Salmo salar) fed a carbohydrate-rich diet exhibit suboptimal growth performance, along with other metabolic disturbances. It is well known that gut microbes play a pivotal role in influencing metabolism of the host, and these microbes can be modified by the diet. The main goal of the present study was to determine the effect of feeding graded levels of digestible carbohydrates to Atlantic salmon on the distal intestine digesta microbiota at 3 sampling times (i.e., weeks 4, 8 and 12), during a 12-week trial. A low carbohydrate-to-high protein diet (LC/HP, 0% wheat starch), a medium carbohydrate-to-medium protein diet (MC/MP, 15% wheat starch) or a high carbohydrate-to-low protein diet (HC/LP, 30% wheat starch) was fed to triplicate fish tanks (27 to 28 fish per tank). We performed an in-depth characterization of the distal intestine digesta microbiota. Further, growth parameters, liver histology and the expression of genes involved in hepatic neolipogenesis in fish were measured. Fish fed a HC/LP diet showed greater hepatosomatic and viscerosomatic indexes (P = 0.026 and P = 0.018, respectively), lower final weight (P = 0.005), weight gain (P = 0.003), feed efficiency (P = 0.033) and growth rate (P = 0.003) compared with fish fed the LC/HP diet. Further, feeding salmon a high digestible carbohydrate diet caused greater lipid vacuolization, steatosis index (P = 0.007) and expression of fatty acid synthase (fas) and delta-6 fatty acyl desaturase (d6fad) (P = 0.001 and P = 0.001, respectively) in the liver compared with fish fed the LC/HP diet. Although, the major impact of feeding a carbohydrate-rich diet to Atlantic salmon in beta diversity of distal intestine digesta microbiota was observed at week 4 (HC/LP vs MC/MP and HC/LP vs LC/HP; P = 0.007 and P = 0.008, respectively) and week 8 (HC/LP vs MC/MP; P = 0.04), no differences between experimental groups were detected after 12 weeks of feeding. Finally, at the end of the trial, there was a negative correlation between lactic acid bacteria (LAB) members, including Leuconostoc and Lactobacillus, with hepatic steatosis level, the hepatosomatic and viscerosomatic indexes as well as the expression of fas and d6fad. Weissella showed negative correlation with hepatic steatosis level and the hepatosomatic index. Finally, further research to explore the potential use of LAB as probiotics to improve liver health in carnivorous fish fed fatty liver-induced diet is warranted.
Keywords: Microbiotica; Microbiome; Steatosis; Atlantic salmon; Lactic acid bacteria; Probiotics